Neoplastic and pre-neoplastic lesions of the oesophagus and gastro-oesophageal junction: Review - Grillo, Federica; Mastracci, Luca; Saragoni, Luca; Vanoli, Alessandro; Limarzi, Francesco; Gullo, Irene; Ferro, Jacopo; Paudice, Michele; Parente, Paola; Fassan, Matteo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Oesophageal and gastro-oesophageal junction (GOJ) neoplasms, and their predisposing conditions, may be encountered by the practicing pathologist both as biopsy samples and as surgical specimens in daily practice. Changes in incidence of oesophageal squamous cell carcinomas (such as a decrease in western countries) and in oesophageal and GOJ adenocarcinomas (such as a sharp increase in western countries) are being reported globally. New modes of treatment have changed our histologic reports as specific aspects must be detailed such as in post endoscopic resections or with regards to post neo-adjuvant therapy tumour regression grades. The main aim of this overview is therefore to provide an up-to-date, easily available and clear diagnostic approach to neoplastic and pre-neoplastic conditions of the oesophagus and GOJ, based on the most recent available guidelines and literature.